Interaction between intense pulsed light and skin: data from an animal model - Faustino-Rocha, Ana Isabel (2021)
Background: Although its effects remain unknown, the intense pulsed light (IPL) has been extensively used in dermatology and esthetics. Purpose: This study aimed to address the impact of IPL in neoplastic lesions using an animal model. Methodology: All experiments followed the European and National legislation. Sixteen ICR female DBA/2JRccHsd mice were randomly assessed to two experimental groups: IPL-exposed (n=8) and non-exposed (n=8). The mice dorsal region was shaved using a machine clipper. The carcinogen 7,12-dimethylbenz[a] anthracene (DMBA; 2mM, single dose) and 12-O-tetradecanoylphorbol-13-acetate (TPA; 100mM, twice a week, for 22 weeks) were applied to all animals. Moreover, IPL-exposed animals were applied with IPL (intensity of 2J/cm2, twice a week, for 22 weeks). At the sacrifice, skin samples were collected and processed for histological analysis. Data was analyzed with SPSS. Results: IPL-exposed mice developed a lower number of skin lesions when compared with non-IPL-exposed animals (28 versus 46 lesions) (p=0.036). Each group presented 8 preneoplastic epidermal lesions (epidermal hyperplasia). The number of neoplastic lesions was lower in IPL-exposed mice than in non-IPL-exposed ones (20 versus 38 lesions) (p=0.018). Papilloma grade II was the neoplastic epidermal lesion most frequently observed in both groups (9 in IPL-exposed mice versus 19 in non-IPL-exposed mice) (p=0.059). Despite this, the number of microinvasive squamous carcinoma was higher in IPL-exposed animals (3 in IPL-exposed mice versus 1 in non-IPL-exposed mice). Conclusion: The results suggest that IPL exposition may inhibit skin carcinogenesis, but its use may promote malignant conversion of skin lesions.